The Role of The Government in Supporting Increasing the Quality of Children Care Patterns in Indonesia - Fia Dhatul Prima Kusuma; Bakhrul Khair Amal (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
The type of parenting who doesn't suitable will badly the development, protection and fulfilment of children's rights. Parenting style also plays a role in the process of socialization on children to develop good behavior. The type of parenting who doesn't suitable caused a child does juvenile delinquency, and other criminal behavior. However, Indonesia doesn’t have Act or regulation that concern about parenting standard to improve the quality of child development. In fact, Act or regulation that concern about parenting standard can became reference for everything involving the development, protection and fulfilment of children's rights in Indonesia